Assessing the Location of Ionic and Molecular Solutes in a Molecularly Heterogeneous and Nonionic Deep Eutectic Solvent - Chen, Xiaobing (J Phys Chem B, 2020)
[Image: see text] Deep eutectic solvents (DES) are emerging sustainable designer solvents viewed as greener and better alternatives to ionic liquids. Nonionic DESs possess unique properties such as viscosity and hydrophobicity that make them desirable in microextraction applications such as oil-spill remediation. This work builds upon a nonionic DES, NMA–LA DES, previously designed by our group. The NMA–LA DES presents a rich nanoscopic morphology that could be used to allocate solutes of different polarities. In this work, the possibility of solvating different solutes within the nanoscopically heterogeneous molecular structure of the NMA–LA DES is investigated using ionic and molecular solutes. In particular, the localized vibrational transitions in these solutes are used as reporters of the DES molecular structure via vibrational spectroscopy. The FTIR and 2DIR data suggest that the ionic solute is confined in a polar and continuous domain formed by NMA, clearly sensing the direct effect of the change in NMA concentration. In the case of the molecular nonionic and polar solute, the data indicates that the solute resides in the interface between the polar and nonpolar domains. Finally, the results for the nonpolar and nonionic solute (W(CO)(6)) are unexpected and less conclusive. Contrary to its polarity, the data suggest that the W(CO)(6) resides within the NMA polar domain of the DES, probably by inducing a domain restructuring in the solvent. However, the data are not conclusive enough to discard the possibility that the restructuring comprises not only the polar domain but also the interface. Overall, our results demonstrate that the NMA–LA DES has nanoscopic domains with affinity to particular molecular properties, such as polarity. Thus, the presented results have a direct implication to separation science.